SHELF LIFE OF Spirulina BISCUIT WITH DIFFERENT PACKAGING - Moulitya Dila Astari; Dewita '; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The aim of this study was to determine shelf life prediction of spirulina biscuitwith different kinds of packaging (HDPE and aluminum foil). The method used isArrhenius, storage at a temperature of 25ºC and 35ºC with an interval ofobservation time is 5 days for 30 days. The parameters analyses are fat contentand peroxide value. The results showed that based on the parameters of the fatcontent the packaging that can maintain the quality of the biscuit is aluminum foilpackaging when stored at 35°C that can last for 52 days 4 hours 49 minutes.Keywords: spirulina biscuit, shelf life, HDPE, aluminum foil